Carascynol A, a hybrid of caryophyllane-type terpenoid and a C6 unit degraded by polyprenylated acylphloroglucinols from Hypericum ascyron - Ya-Li Hu; Xing-Ren Li; Gang Xu (Natural Products and Bioprospecting, 2022)
Abstract Carascynol A, an unprecedented 4/9/8 ring system hybrid with a peroxide bridge, was characterized from Hypericum ascyron. The architecture contains a caryophyllane-type moiety and a C6 unit derived from polyprenylated acylphloroglucinols. Its structure and absolute configuration were determined by comprehensive spectroscopic and X-ray diffraction data. Biologically, compound 1 inhibited cell proliferation in LoVo, SW480, and HCT116 cell lines (IC50 = 12.30–24.57 µM). Graphical Abstract